A new agarose-based microsystem to investigate cell response to prolonged confinement. Issue 21 (25th September 2020) - Prunet, A.; Lefort, S.; Delanoë-Ayari, H.; Laperrousaz, B.; Simon, G.; Barentin, C.; Saci, S.; Argoul, F.; Guyot, B.; Rieu, J.-P.; Gobert, S.; Maguer-Satta, V.; et al.
Abstract : A unique tool to analyze the role of long-term effects of mechanical confinement in normal and pathological conditions. Abstract : Emerging evidence suggests the importance of mechanical stimuli in normal and pathological situations for the control of many critical cellular functions. While the effect of matrix stiffness has been and is still extensively studied, few studies have focused on the role of mechanical stresses. The main limitation of such analyses is the lack of standard in vitro assays enabling extended mechanical stimulation compatible with dynamic biological and biophysical cell characterization. We have developed an agarose-based microsystem, the soft cell confiner, which enables the precise control of confinement for single or mixed cell populations. The rigidity of the confiner matches physiological conditions and its porosity enables passive medium renewal. It is compatible with time-lapse microscopy, in situ immunostaining, and standard molecular analyses, and can be used with both adherent and non-adherent cell lines. Cell proliferation of various cell lines (hematopoietic cells, MCF10A epithelial breast cells and HS27A stromal cells) was followed for several days up to confluence using video-microscopy and further documented by Western blot and immunostaining. Interestingly, even though the nuclear projected area was much larger upon confinement, with many highly deformed nuclei (non-circular shape), cell viability, assessed by live and dead cell staining, was unaffected for up to 8 days in the confiner. However, there was a decrease in cell proliferation upon confinement for all cell lines tested. The soft cell confiner is thus a valuable tool to decipher the effects of long-term confinement and deformation on the biology of cell populations. This tool will be instrumental in deciphering the impact of nuclear and cytoskeletal mechanosensitivity in normal and pathological conditions involving highly confined situations, such as those reported upon aging with fibrosis or during cancer.